ANALISIS SENTIMEN TERHADAP ULASAN PENGGUNAAN SHOPEE MELALUI TWEET PADA TWITTER MENGGUNAKAN ALGORITMA NAÏVE BAYES - Muflih, Hilmy Zhafran; Al Assyam, Hafizh Dhery; Pangestu, Faisal Akbar; Kamayani, Mia (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
The increasing use of the internet among the public is because it is a means to carry out various activities, one of which is buying and selling online or known as e-commerce. One of the largest e-commerce in Indonesia is Shopee. Shopee offers various features for its users. The large number of shopee users results in the large number of responses given to shopee, so the researcher wants to carry out a sentiment analysis process regarding user responses to shopee, whether the response of shopee users is negative or positive. The responses or opinions of Shopee users are taken from tweets in the Twitter application. Tweets typed and written and published by Twitter users about shopee. In this study, researchers used the RapidMiner application to collect tweets data from Twitter users and to apply the Naïve Bayes algorithm. The researcher collected 200 data regarding shopee from Twitter. The results obtained from sentiment analysis using the Naïve Bayes algorithm get 78% negative sentiment and 22% positive sentiment from 200 datasets. The process of testing the Naïve Bayes algorithm using the confusion matrix obtains an accuracy value of 77.50%.